PENGARUH LOCUS OF CONTROL DAN KOMPLEKSITAS TUGAS DENGAN SIFAT MACHIAVELLIAN SEBAGAI PEMODERASI TERHADAP PERILAKU DISFUNGSIONAL AUDIT DI KAP KOTA DENPASAR - I Wayan Kartana (Akuntansi dan Teknologi Informasi, 2021)
Independent auditor services are needed to determine the reliability of the financial statements presented by management and to give an opinion towards the financial statements in a credible manner, so that they can be trusted and obtain larger market share. In addition, the reporting process must also be effective by employing competent and objective independent auditors to give high quality audit based on the Professional Standards of Public Accountants (SPAP) and the Code of Ethics (IAPI,2016). On the other side, non-compliance towards SPAP and the Code of Ethics can reduce the audit quality. The non-compliance to the standards leads to violation cases and financial scandals, which inhibits the credibility of the auditors. This study aims to examine the effect of locus of external and task complexity towards the dysfunctional audit behavior moderated by Machiavellian. This research was conducted on auditors that was registered at the Public Accounting Firm (KAP) in Denpasar using the PLS-SEM analysis and with the support of SmartPLS 3.0. Software. The results showed that the auditor’s dysfunctional behavior can be caused by the variations of external locus, the complexity of the task which interacts with Machiavellian.